2021
DOI: 10.1038/s41586-021-03336-2
|View full text |Cite
|
Sign up to set email alerts
|

Genomic insights into the formation of human populations in East Asia

Abstract: The deep population history of East Asia remains poorly understood due to a lack of ancient DNA data and sparse sampling of present-day people 1 , 2 . We report genome-wide data from 166 East Asians dating to 6000 BCE – 1000 CE and 46 present-day groups. Hunter-gatherers from Japan, the Amur River Basin, and people of Neolithic and Iron Age Taiwan and the Tibetan plateau are linked by a deeply-splitting lineage likely reflecting a Late Pleistocene coastal m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
366
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 274 publications
(457 citation statements)
references
References 71 publications
32
366
1
1
Order By: Relevance
“…S9 D, E, and J)). This is consistent with the recent analysis of ancient individuals from East Asia, which revealed gene flow between populations across various points of time (18)(19)(20) and showed that there is some genetic affiliation between nEAs and southern East Asians, including Liangdao individuals (19).…”
Section: Cordillerans Represent the Least Admixed Basal East Asian Grsupporting
confidence: 92%
See 1 more Smart Citation
“…S9 D, E, and J)). This is consistent with the recent analysis of ancient individuals from East Asia, which revealed gene flow between populations across various points of time (18)(19)(20) and showed that there is some genetic affiliation between nEAs and southern East Asians, including Liangdao individuals (19).…”
Section: Cordillerans Represent the Least Admixed Basal East Asian Grsupporting
confidence: 92%
“…We find no genetic evidence for an association between currently established dates for the arrival and expansion of paddy field rice agriculture (∼2 to 3 kya) (31,32) and the demographic movement of people from the South China-Taiwan greater area into the Philippines. Given the genetic makeup of the Liangdao-2 woman and other ancient Taiwanese and southern East Asian individuals (18) who all present some nEA ancestry, the most parsimonious explanation is that Cordillerans entered the Philippines prior to the nEA gene flow. This observation sets a boundary for the date of arrival of Cordillerans in the Philippines, at least ∼7 to 8 kya or earlier, indicating that early Cordillerans in the Philippines were mobile hunter-gatherers.…”
Section: Discussionmentioning
confidence: 99%
“…They also revealed significant population stratification among East Asians according to language categories. Next, we focused on the population differentiation between Huis and East Asians (Wang et al, 2021). As shown in Supplementary Table 15, most statistically positive f 4 values observed among modern Eastern panels based on the merged 1,240 K dataset demonstrated that the Boshu Huis harbored more East Asian-derived ancestry than their respective predefined comparative populations, which is consistent with the genetic affinity identified via the outgroup f 3 statistics and pairwise f 4 analysis based on the Human Origin 16).…”
Section: Differentiated Demographic Histories Estimated From F 4 Statisticssupporting
confidence: 65%
“…A previous study of modern and ancient East Asians including the seven Jomon individuals suggest that the Jomon people have two ancestry components from ancient East Asians, i.e. the Interior South ancestry and the Coastal ancestry 33 . Considering the results of this study and previous studies, at least the ancestral population of Jomon people seem to have migrated to the Japanese archipelago from the south of East Eurasia (southern parts of the Himalayas) via the southern of China, although it cannot be concluded whether they passed through coastal or inland areas.…”
Section: Genetic Relationships Between the Jomon People And Other East Asiansmentioning
confidence: 94%